Prinsip Hukum Islam dan Tata Kelola Pertambangan Berkelanjutan di Indonesia: Suatu Kerangka Analiti - Itishan, Bani Adam; Kurniaty; Musyfikah Ilyas (Progressive Law Review, 2025)
Indonesia's considerable mineral resources including coal, nickel, copper, and bauxite are pivotal to economic development and the worldwide green energy supply chain. Nonetheless, expedited extraction has resulted in significant environmental degradation, socio-economic disruption, and legal-ethical issues, especially in areas facing deforestation, water contamination, habitat fragmentation, and community displacement. These effects underscore the urgent necessity for a governance framework that enforces regulatory compliance while incorporating ethical and environmental accountability. This study analyzes the potential of Islamic legal concepts to provide a normative and ethical framework for enhancing sustainable mining governance in Indonesia. This study aims to achieve three objectives: (1) to assess the environmental, social, and economic consequences of mineral extraction; (2) to investigate Islamic legal principles pertinent to resource governance, including maqāṣid al-sharī‘ah, khilāfah, milkiyyah ‘āmmah, ḥifẓ al-bī’ah, and hisbah; and (3) to develop a cohesive analytical framework that harmonizes Islamic jurisprudence with Indonesia’s mining regulatory framework. This article utilizes a qualitative narrative-descriptive methodology, using statutory and regulatory texts, ancient and modern Islamic legal sources, MUI fatwas, environmental reports, and recent academic research. The data were systematically categorized by theme and examined using triangulation to confirm the coherence and validity of the arguments.The results indicate that Islamic law provides a thorough ethical framework that can effectively address governance deficiencies in Indonesia's mining industry. Principles such as lā ḍarar wa lā dirār and dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ offer robust ethical basis for more stringent environmental regulations, while hisbah legitimizes governmental involvement to avert ecological damage. Incorporating these concepts with national mining rules and ESG standards can improve environmental protection, guarantee equitable benefit sharing, fortify community rights, and advance intergenerational justice. This research finishes by presenting a normative-ethical framework for sustainable mining that aligns positive law with Islamic environmental jurisprudence.